(2E,20E)-1,10-(1,4-Phenylene)bis[3-(3-chlorophenyl)- prop-2-en-1-one] - Rajendraprasad, S.; Chidan Kumar, C. S.; Chandraju, S.; Lokanath, N. K.; Ching, Kheng Quah; Naveen, S.; Abdoh, Muneer (International Union of Crystallography, 2017)
The title bis-chalcone compound, C24H16Cl2O2, crystallizes with one halfmolecule in the asymmetric unit. The molecule has crystallographic inversion symmetry and lies about an inversion centre at the centroid of the central benzene ring. The olefinic double bonds adopt E configurations. The s-trans conformation of the central C—C bond of the enone group is confirmed by a C—C—C C torsion angle of 162.88 (17).